The class ceiling why it pays to be privileged - Friedman, Sam. (Chicago Policy Press, 2019)
Politicians continually tell us that anyone can get ahead. But is that really true? This important book takes readers behind the closed doors of elite employers to reveal how class affects who gets to the top. Friedman and Laurison show that a powerful 'class pay gap' exists in Britain's elite occupations. Even when those from working-class backgrounds make it into prestigious jobs they earn, on average, 16% less than colleagues from privileged backgrounds. But why is this the case? Drawing on 175 interviews across four case studies--television, accountancy, architecture, and acting--they explore the complex barriers facing the upwardly mobile
Includes bibliographical references (pages 321-358) and index.
Keywords: Discrimination in employment--Great Britain